Firn core density and ice content at sites along the lower Expéditions Glaciologiques Internationales au Groenland (EGIG) line, Western Greenland, 2023 - Joel Harper; Neil Humphrey (Arctic Data Center, 2023)
This archive contains data collected at sites located along the lower elevation portion of the Expéditions Glaciologiques Internationales au Groenland (EGIG) line, Western Greenland Ice Sheet. The data include the physical stratigraphy measured in firn cores extending to depths of up to ~30 meter (m) with measurements of firn density and refrozen ice content. The data were collected as part of an Arctic Observing Network (AON) project funded by the U.S. National Science Foundation. Each of the study sites is located in the Greenland Ice Sheet’s Percolation Zone, the outer flanks of the accumulation zone that experiences surface melt during the summer period. Data collection for this AON project began in 2022, and is expected to continue through 2025. This dataset will be associated with additional datasets, including physical stratigraphy and density measured in ice cores and firn temperature time series measured in core holes, as they become available in future years. Additional sites with will be added in future years, and additional data from existing sites will be collected.